2011
DOI: 10.1103/physrevd.84.083513
|View full text |Cite
|
Sign up to set email alerts
|

Geodesically complete analytic solutions for a cyclic universe

Abstract: We present analytic solutions to a class of cosmological models described by a canonical scalar field minimally coupled to gravity and experiencing self interactions through a hyperbolic potential. Using models and methods inspired by 2T-physics, we show how analytic solutions can be obtained in flat/open/closed Friedmann-Robertson-Walker universes.Among the analytic solutions, there are many interesting geodesically complete cyclic solutions in which the universe bounces at either zero or finite sizes. When g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 33 publications
(158 reference statements)
3
74
0
Order By: Relevance
“…Our goal in this paper is to provide a full set of analytic solutions that give all possible configurations of a homogeneous and isotropic universe as a function of time. This expands on our previous work in [13][14][15] by including additional degrees of freedom, in particular radiation. The effects of anisotropy are discussed elsewhere [16,17].…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our goal in this paper is to provide a full set of analytic solutions that give all possible configurations of a homogeneous and isotropic universe as a function of time. This expands on our previous work in [13][14][15] by including additional degrees of freedom, in particular radiation. The effects of anisotropy are discussed elsewhere [16,17].…”
Section: Introductionmentioning
confidence: 52%
“…The method, which is based on conformal symmetry, was introduced in previous papers [13]- [17]. It was applied to the cases of the flat and curved isotropic Friedmann universes without radiation or matter [14]. It was also applied to the case of an anisotropic universe in the absence of the potential energy, but with the inclusion of radiation [17].…”
Section: Introductionmentioning
confidence: 99%
“…II D, with limited success. An intriguing proposal by Bars et al in [55][56][57][58][59][60][61] allows to trace the evolution of the universe unambiguously through a singular bounce via a brief antigravity phase, see Sec. II E; however, a computation of observables in this framework has not been performed yet.…”
Section: B What Is Used To Get a Bounce?mentioning
confidence: 99%
“…In a series of papers, Bars et al [55][56][57][58][59][60][61] showed that theories motivated by the minimal conformal extension of the standard model with scalar fields coupled to gravity can be lifted to a Weyl-invariant theory that allows the cosmological evolution to be unambiguously traced through a big-crunch/big-bang (singular) transition. Here the classical evolution can be followed in a homogeneous, but potentially anisotropic (e.g.…”
Section: E Antigravitymentioning
confidence: 99%
“…Note that the interest to the study of the possibility of crossing of such singularities is growing and some models treating this phenomenon have been elaborated during last few years [45].…”
Section: Discussionmentioning
confidence: 99%